Strategi Pertumbuhan Gereja Menurut Kisah Para Rasul 4:32-37 Dan Implikasinya Bagi Gereja Masa Kini - Jultriani Sombo Lola; Febrianto Rompis (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
The church is a gathering place for believers to glorify God as a sign of gratitude for God's inclusion in this world. Therefore the Church must grow and unite, because the one who formed the early church was God himself. Therefore the church must be able to become a channel of blessings like God's mission as the salt and light of the world, the church is not a haven for people who do not know God but the church is a place where God's children receive the gift of blessings from God.